Grandfathers Matter(ed): Occupational Mobility Across Three Generations in the US and Britain, 1850–1911. (11th June 2018) - Long, Jason; Ferrie, Joseph
Abstract: Nearly all intergenerational mobility studies focus on fathers and sons. The possibility that the process is more than simply two‐generational (AR(1)) has been difficult to assess because of the lack of the necessary multi‐generational data. We remedy this shortcoming with new data that links grandfathers, fathers and sons in Britain and the US between 1850 and 1910. We find that grandfathers mattered: even controlling for father's occupation, grandfather's occupation significantly influenced the occupation of the grandson. For both Britain and the US in this time period, therefore, assessments based on two‐generation estimates significantly overstate the true amount of social mobility.